Micellar liquid chromatographic determination of penicillins in pharmaceuticals - P. Srisom (2018)
A new, simple, rapid and specific micellar liquid chromatographic (MLC) method was developed and validated for the determination of amoxicillin, ampicillin, cloxacillin and dicloxacillin in pharmaceutical formulations. Separation was achieved isocratically on an Ultra C18column (150 mm × 4.6 mm) utilizing a mobile phase of 25 mM SDS-2% (v/v) 1-butanol in phosphate buffer (pH 5.0) at a flow rate of 1.0 mL min-1with UV detection at 200 nm. Validation experiments were performed to demonstrate linear ranges, accuracy, precision, robustness, limit of detection (LOD) and limit of quantification (LOQ). The method was applied to the determination of these penicillins in various pharmaceutical formulations. The results compared favorably with those obtained by the official methods, and were in agreement with the declared compositions. The method can be used for quality control assay of the studied penicillins. © 2007 Friedr. Vieweg & Sohn Verlag/GWV Fachverlage GmbH.